President Nursultan Nazarbayev`s program article “The course towards future: Modernization of public consciousness” – ideology, value and political aspects - Gulnar Askeyeva, Bibigul Byulegenova., Nurbek Pussyrmanov, Indira Rystina, Bibigul Bulegenova, (Opción, 2019)
The modernization processes of the state political system are simultaneously experiencing two situations with the exception of old values and the introduction of new values. The article completely defines the direction in modernization of public consciousness and national-ideological unification. This is a desire to get rid of the Soviet traces and ideological syndrome in the post-soviet space, as well as a desire to think in a new independent mindset. Continuous implementation of political reforms in this direction promotes democratization of the Kazakhstan society, ideological and value strengthening and full formation of signs of civil society.